PENGARUH BANTUAN MODAL USAHA DAN PENDAMPINGAN USAHA TERHADAP MOTIVASI MENJADI MUZAKKI DENGAN TINGKAT PENDAPATAN USAHA MUSTAHIK SEBAGAI VARIABEL INTERVENING - Muhammad Hasan Zain; Adi Mansah (FEB Universitas Muhammadiyah Jakarta, 2021)
The purpose of this study is to determine: (1) The direct effect of capital assistance and mentoring on mustahik business income levels. (2) The direct effect of capital assistance and business assistance on motivation to become muzakki. (3) Direct effect of capital assistance on motivation to become muzakki. (4) Direct effect of business assistance on motivation to become muzakki. (5) The direct effect of mustahik's business income level on the motivation to become muzakki. (6) The indirect effect of capital assistance on the motivation to become muzakki and the level of business income for mustahik as an intervening variable. (7) Business assistance towards motivation to become muzakki with the income level of mustahik business as an intervening variable. This type of research is a quantitative study which refers to the calculation of the numbers obtained from a questionnaire with a Likert scale. The sample in this study was the fostered mustahik registered from 2018-2019 at the BAZNAS Institute for Economic Empowerment (LPEM). The sample selection used nonprobability sampling with a quota sampling method with 116 mustahiks consisting of 3 programs. The data analysis technique uses path analysis. The results of this study indicate that (1) Hypothesis 1 is accepted with the line coefficient of capital assistance to the level of business income of 0524. (2) Hypothesis 2 is accepted with the coefficient of business assistance pathway to the level of mustahik business income of 0.393. (3) Hypothesis 3 is rejected with the path coefficient of capital assistance on motivation to become muzakki of 0.030. (4) Hypothesis 4 is accepted with the coefficient of business assistance pathway on motivation to become muzakki of 0.240. (5) Hypothesis 5 is accepted with the path coefficient. The income level of mustahik's business on motivation to become muzakk is 0.159. (6) Meanwhile, the income level of mustahik business can mediate between capital assistance and motivation to become muzakki of 0.028. (7) Mustahik business income level cannot mediate between business assistance and motivation to become muzakki for mustahik assisted by the BAZNAS Economic Empowerment Institute (LPEM).